Pekerja Anak dan Goncangan Pertanian di Indonesia - Kharisma, Bayu (Jurnal Ekonomi Kuantitatif Terapan; 2017: Vol. 10, No. 2, Agustus 2017 (pp. 110 - 252)DO - 10.24843/JEKT.2017.v10.i02.p03, 2017)
The aims of this research is to determine the effect of crop loss shocks against child labor and the role of the assets held by households, both farm and non-farm business can reduce the impact of these shocks. The results showed that the effects of crop loss shocks insignificantly affect child labor at the age of 5-14 years. This indicates that in the event of crop loss shocks, households do not use a coping strategy by increasing child labor to dampen the shocks. Meanwhile, assets used for non-farm business was able to reduce the demand for child labor. On the other hand, farm business assets has positive effect on working children aged 5-14. This indicates the wealth effect phenomenon that occurred in Indonesia.
Keywords: bencana gagal panen, pekerja anak, aset farm business, non farm business, wealth effect